Early life factors and oral microbial signatures define the risk of caries in a Swedish cohort of preschool children - Carsten Eriksen; Katarina Boustedt; Si Brask Sonne; Jovanna Dahlgren; Karsten Kristiansen; Svante Twetman; Susanne Brix; Josefine Roswall (Scientific Reports, 2024)
Abstract The oral cavity harbors complex communities comprising bacteria, archaea, fungi, protozoa, and viruses. The oral microbiota is establish at birth and develops further during childhood, with early life factors such as birth mode, feeding practices, and oral hygiene, reported to influence this development and the susceptibility to caries. We here analyzed the oral bacterial composition in saliva of 260 Swedish children at two, three and five years of age using 16S rRNA gene profiling to examine its relation to environmental factors and caries development at five years of age. We were able to assign the salivary bacterial community in each child at each time point to one of seven distinct clusters. We observed an individual dynamic in the development of the oral microbiota related to early life factors, such as being first born, born by C-section, maternal perinatal antibiotics use, with a distinct transition between three and five years of age. Different bacterial signatures depending on age were related to increased caries risk, while Peptococcus consistently linked to reduced risk of caries development.